Pendampingan Literasi Digital Berbasis Fitrah untuk Mengurangi Risiko Kecanduan Gadget pada Anak Usia Dini - Sofino, Sofino; Gusti, Ririn; Mantili Hutauruk, Lenni; Yunita, Wiwin; Pradikto, Bayu (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
The rapid development of digital technology has had a significant impact on family parenting patterns, particularly with young children's use of gadgets. Children often experience excessive use of digital devices without supervision, as many parents lack adequate digital literacy skills. This community service activity aims to improve parents' understanding and skills in managing their children's use of gadgets through a natural digital literacy approach. The activity was carried out at PAUD SPNF-SKB, Central Bengkulu Regency, on October 8-22, 2025, involving 26 parents of PAUD students. Participants engaged in hands-on workshops that demonstrated effective strategies for setting boundaries and fostering healthy tech habits. By empowering parents with knowledge, the initiative sought to create a more balanced relationship between children and their digital devices, ultimately enhancing family dynamics and children's overall well-being. The implementation methods included participatory counseling, interactive training, and assistance through home visits and online communication. The results of the activity showed a significant increase in parents' knowledge and attitudes regarding digital parenting. The average score on the pretest was 5.15 (42.9%), and it went up to 10.77 (89.8%) on the posttest. During the training phase, all participants successfully developed a digital family agreement containing rules for gadget use at home, with 77% committing to consistent implementation and 33% planning to implement it gradually. The results of the mentoring showed a decrease in the duration of children's gadget use from an average of 3-4 hours per day to 1-1.5 hours per day, as well as an increase in children's interest in non-digital activities such as reading, drawing, and playing outdoors. In addition, 77% of participants reported an increase in emotional closeness with their children after applying the principles of digital literacy based on human nature. This activity proves that the natural-based digital literacy approach is effective in improving parental competencies in the digital age while strengthening family relationships.